2010
DOI: 10.4315/0362-028x-73.9.1613
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antimicrobial Resistance Profiles of Salmonella Species in Retail Meat Products

Abstract: In the present study, a total of 225 retail meat products (poultry meat, ground beef, and beef samples) were tested for the prevalence of Salmonella. Of these, 50 (22.2%) were positive for Salmonella. Overall, the pathogen was detected in 22 (29.3%) samples of poultry meat (n = 75), 16 (21.3%) samples of ground beef (n = 75), and 12 (16%) samples of beef (n = 75). The most common isolate was Salmonella enterica serovar Typhimurium (9.8%), followed by S. bongori species (8.9%) and S. enterica subsp. diarizonae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 19 publications
6
27
3
Order By: Relevance
“…in chicken products obtained by other authors varied between 0 and 100% [23,24]. In this study, the overall prevalence of Salmonella in chicken meat and giblets was 19.8% (111/560).The contamination rate of chicken meat samples (29%) is in agreement with results reported in Belgium [25], the United Kingdom [26], Iran [27],China [28], Turkey [29], Iraq [30], and the Russian Federation [31], but lower than results found in Iran [20,32] and many other countries, such as China, Mexico, and Poland [16,18,[33][34][35]. The incidence of Salmonella spp.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…in chicken products obtained by other authors varied between 0 and 100% [23,24]. In this study, the overall prevalence of Salmonella in chicken meat and giblets was 19.8% (111/560).The contamination rate of chicken meat samples (29%) is in agreement with results reported in Belgium [25], the United Kingdom [26], Iran [27],China [28], Turkey [29], Iraq [30], and the Russian Federation [31], but lower than results found in Iran [20,32] and many other countries, such as China, Mexico, and Poland [16,18,[33][34][35]. The incidence of Salmonella spp.…”
Section: Resultssupporting
confidence: 91%
“…Despite increasing resistance to commonly used antibiotics in animal and human medicine globally, the numbers of multidrug-resistant Salmonella isolates continues to increase [2,11]. The percentage of multidrug-resistant Salmonella strains observed in this study (62.2%) is higher than that reported in Italy (2.3%) [49] and Iran (23.5%) [20], although lower than that found in Morocco (75.43%) [17], Portugal (75%) [50], Turkey (100%) [13,16,29], Spain (100%) [2], Brazil (100%) [51], Nepal (100%) [52], the United States (92%) [53], Mexico (85.4%) [34], and China (80%) [54]. In the present study, all S. Hadar isolates showed multidrug resistance to nalidixic acid and tetracycline (Table 4).…”
Section: Resultsmentioning
confidence: 51%
“…All isolates showed a relatively high degree of sensitivity to ciprofloxacin (92%) and ceftriaxone (95%), (commonly used fluoroquinolones and cephalosporins antibiotics), which may reflect restricted use of them in avian. This finding is in accordance with those reported from Vietnam (17,18) and is in contrast to report from Turkey (19).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 93.75% of the Salmonella isolates was classified as multidrug resistant. Our results were relatively high according to some studies [15,16] while showed similarities to others [4,6] .…”
Section: Discussionsupporting
confidence: 84%